2022
DOI: 10.2147/prbm.s341068
|View full text |Cite
|
Sign up to set email alerts
|

The Paradoxical Effects of the Contagion of Service-Oriented Organizational Citizenship Behavior

Abstract: Purpose Previous research on the service-oriented organizational citizenship behavior (OCB) of employees has mainly focused on the examination of its driving factors, and has ignored the consequences that it may bring to the workplace. To bridge this research gap, by shifting the focus to the event observers, a double-edged sword model is constructed in the present study, which helps explain whether, when, and why the service-oriented OCB of coworkers is contagious. Methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…Moreover, as shown in Table 3 , the correlation coefficient of PIU, PD, and sociability is less than the square root of their AVE, which further confirms the good discrimination validity of the variables in this study. 83 …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, as shown in Table 3 , the correlation coefficient of PIU, PD, and sociability is less than the square root of their AVE, which further confirms the good discrimination validity of the variables in this study. 83 …”
Section: Resultsmentioning
confidence: 99%
“…Organizational Citizenship Behavior (OCB) is an individual's contribution that exceeds role demands in the workplace, involving several behaviors, including helping others, volunteering for extra tasks, complying with workplace rules and procedures. This behavior describes "personnel added value" which is a form of prosocial behavior, namely social behavior that is positive, constructive, and meaningfully helpful (Guo et al, 2022). Organizational Citizenship Behavior (OCB) is a form of work behavior that is usually not visible or considered.…”
Section: Strategic Competence According Tomentioning
confidence: 99%
“…Previous research has shown that organizational service performance in the hotel industry has a positive impact on SOCB [32]. Colleagues' SOCB can influence other employees, prompting them to partake in SOCB, subsequently promoting the enterprise's service performance [33]. A positive leadership style promotes employees' SOCB [34,35].…”
Section: Service-oriented Organization Citizenship Behavior (Socb)mentioning
confidence: 99%